Implicit Processes, Self-Regulation, and Interventions for Behavior Change - St Quinton, Tom; Brunton, Julie A. (Frontiers in Psychology, 2017)
The ability to regulate and subsequently change behavior is influenced by both reflective and implicit processes. Traditional theories have focused on conscious processes by highlighting the beliefs and intentions that influence decision making. However, their success in changing behavior has been modest with a gap between intention and behavior apparent. Dual-process models have been recently applied to health psychology; with numerous models incorporating implicit processes that influence behavior as well as the more common conscious processes. Such implicit processes are theorized to govern behavior nonconsciously. The article provides a commentary on motivational and volitional processes and how interventions have combined to attempt an increase in positive health behaviors. Following this, nonconscious processes are discussed in terms of their theoretical underpinning. The article will then highlight how these processes have been measured and will then discuss the different ways that the nonconscious and conscious may interact. The development of interventions manipulating both processes may well prove crucial in successfully altering behavior.